The influence way of learning, reading and studying the use of school facilities on student learning outcomes Integrated IPS - komala sari komala sari; yon rizal; teddy rusman (JEE (Jurnal Edukasi Ekobis), 2013)
This study aims to determine whether there is influence of learning styles, interest in reading and learning in school utilization of the learning outcomes of Integrated Social Science. The method used in this research is descriptive method of verification with ex post facto approach and survey.Berdasarkan analysis of the results obtained. (1) There is the influence of learning on learning outcomes semester of eighth grade students of SMP Bina Mulya, (2) There is an effect on learning outcomes of interest in reading class VIII semester junior Bina Mulya, (3) There is a study on the effect of the use of school facilities to the results junior High School eighth grade student Bina Mulya, (4) There is an effect way of learning, reading and studying the use of school facilities on student learning outcomes Integrated IPS SMP Bina Mulya eighth grade.Keywords: How to Learn, Reading Interest, Means and Learning Outcomes